ANALISIS TRANSAKSI BELANJA ONLINE DALAM PERSPEKTIF FIQIH MUAMALAH DAN KEPATUHAN SYARIAH - Lanifa Fauzia Comersyah; Sabrina Oktavia Ramadani; Alyasa Najwa (Taksasila Edukasi Insani, 2025)
This study discusses the concept and online buying and selling transactions that comply with sharia principles. This study aims to analyze the validity of online buying and selling transactions based on the perspective of fiqh muamalah. This study uses qualitative descriptive and literature research methods by examining materials related to the Analysis of Online Shopping Transactions in the Perspective of Fiqh Muamalah and Sharia compliance. The results of the study indicate that online shopping transactions can be considered valid according to sharia if they meet four main requirements, namely the existence of the transacting parties, the existence of ijab and qabul, clarity of the object of the transaction, and a halal purpose. In addition, the principles of transparency, honesty, and freedom from usury and gharar are important requirements in maintaining the justice and validity of online buying and selling according to Islamic law.Keywords : Online buying and selling, Islamic jurisprudence, Sharia compliance, Transaction validity, Offer and acceptance